Penerapan Metode Kunci ABC (Aneka Berhitung Cepat): Pembelajaran Konsep Operasi Perkalian Matematika pada Siswa Sekolah Dasar - Erdawati, Sri; Rahman, Arivaie (Institut Agama Islam Negeri Kendari, 2021)
This article reports the result of a classroom action research focusing on elementary school students’ development in multiplication under Aneka Berhitung Cepat (ABC) key method. Data were gathered from 19 students by means of tests, observations, documentation, and reflection within two cycles under planning, action, observation, and reflection stages.The result ofqualitative analysis showed an increase in students’ participation in learning activities and students’ learning outcomes. This study implies that ABC key method could be of consideration for math teachers to apply in the classroom.Keywords: ABS key method, elementary school, mathematics